Calorie knowledge / Sharifah Maimunah Syed Mud Puad ... [et al.] - Syed Mud Puad, Sharifah Maimunah; A. Rahman, Muhammad Wafi; Ahmad, Mohamad Firdaus; Lamat, Siti Aida; Dahlan, Nur Dalilah; Bakri, Nur Hani Syazwani (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Obesity is becoming a major public health concern in Malaysia. According to the World Health Organization (WHO, 2019), Malaysia has the highest rate of obesity and overweight population among Asian countries, with 64% of males and 65% of females being obese or overweight [1]. Malaysians' poor eating habits, which include a high calorie intake, consumption of energy-dense foods, and a lack of physical activity, contribute to this epidemic. This issue requires effective measures to encourage healthy eating habits that can lower chronic disease risk factors. Nutrition education is an approach to encourage healthy eating habits by delivering nutrition-related knowledge [2]. It is speculated that information which increases knowledge and personal awareness will be productive in inciting behavioural changes [3]. Healthy eating and a well-balanced diet are important aspects of nutrition education. A well-balanced, nutritious diet should supply enough calories and all the essential nutrients to maintain energy balance. Weight gain is caused by a positive energy balance, in which energy intake exceeds expenditure [4]. The main issue with energy balance is the calorie counting for food intake [4]. Most individuals have no idea on how many calories they eat at each meal. Knowing the calorie content can assist an individual to avoid overeating. Dietary calorie information is vital for better nutrition awareness.